Photothermal catalytic dry reforming of methane over Ce‐promoted Ni/NiO heterostructure - Xue, Yao; Dong, Wenjing; Li, Zixian; Ren, Jing; Yang, Zhijia; Peng, Yung‐Kang; Meng, Xianguang; Zhao, Yufei (AIChE journal, 2025)
Photothermal catalytic dry reforming of methane (DRM) provides a sustainable carbon conversion route, but the syngas production rates remain unsatisfactory under low‐temperature conditions. This study reported a layered double hydroxide‐derived Ni–NiO heterojunction catalyst with optimized electronic environments via Ce doping. The Ce‐doped Ni–NiO catalyst exhibited excellent photothermal DRM performance, with H2 and CO production rates of 93.90 and 114.25 mmol g−1 min−1, respectively, and superior 12‐h stability. Mechanistic studies revealed that the Ni–NiO heterojunction activated CH4 and CO2 to form CHx* and O* species, while Ce doping promoted the coupling of these intermediates to CH3O*, enhancing syngas generation. This strategy effectively bonded the intermediate species generated from the reactants, thereby enhancing the conversion of CH4 and CO2 into syngas.